Advances in femtosecond laser technology - Callou TP (Dove Medical Press, 2016)
Thais Pinheiro Callou, Renato Garcia, Adriana Mukai, Natalia T Giacomin, Rodrigo Guimarães de Souza, Samir J Bechara Department of Ophthalmology, University of Sao Paulo, Sao Paulo, Brazil Abstract: Femtosecond laser technology has become widely adopted by ophthalmic surgeons. The purpose of this study is to discuss applications and advantages of femtosecond lasers over traditional manual techniques, and related unique complications in cataract surgery and corneal refractive surgical procedures, including: LASIK flap creation, intracorneal ring segment implantation, presbyopic treatments, keratoplasty, astigmatic keratotomy, and intrastromal lenticule procedures. Keywords: laser therapy, refractive surgical procedures, intracorneal ring, laser in situ keratomileusis, keratoplasty, presbyopia, cataract extraction, astigmatism surgery